2014
DOI: 10.1186/s12929-014-0075-1
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 positively affects tumorigenesis of esophageal squamous cell carcinoma and correlates with poor survival of patients

Abstract: BackgroundPin1 promotes oncogenesis by regulating multiple oncogenic signaling. In this study, we investigated the involvement of Pin1 in tumor progression and in the prognosis of human esophageal squamous cell carcinoma (ESCC).ResultsWe observed that proliferation, clonogenicity and tumorigenesis of CE81T cells were inhibited by Pin1 knockdown. We next analyzed Pin1 expression in clinical ESCC specimens. When compared to the corresponding non-tumor part, Pin1 protein and mRNA levels in tumor part were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In this study, we found that Pin1 is a direct target of 6,7,4 0 -THIF for the suppression of esophageal cancer cell growth. Upregulation of Pin1 levels has been observed clinically and is closely correlated with poor survival of esophageal cancer patients (28). Indeed, we confirmed an overexpression of the Pin1 protein in esophageal cancer cells compared with normal cells (Supplementary Fig.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, we found that Pin1 is a direct target of 6,7,4 0 -THIF for the suppression of esophageal cancer cell growth. Upregulation of Pin1 levels has been observed clinically and is closely correlated with poor survival of esophageal cancer patients (28). Indeed, we confirmed an overexpression of the Pin1 protein in esophageal cancer cells compared with normal cells (Supplementary Fig.…”
Section: Introductionsupporting
confidence: 79%
“…Even though the actual bioactive compounds in soy isoflavones are their metabolites (12), only a few studies have begun to reveal the physiologic activities and identify their modes of action (14)(15)(16). In the case of esophageal cancer, Pin1 has been clearly correlated with prognosis and poor survival of patients (28). Because Pin1 regulates oncogenes, such as c-Jun, p63a, p63nerb B2 (22, 40), the poor prognosis for patients with esophageal cancer was assumed to be associated with Pin1-related oncogene activation.…”
Section: Discussionmentioning
confidence: 99%
“…PIN1 is a central controller in the regulation of proline‐directed phosphorylation, which is a common event relating to tumorigenesis . Overactivation or upregulation of PIN1 contributes to carcinogenesis in the majority of human tumors, including PDAC, whereas alteration of PIN1 single nucleotide polymorphisms (SNP) at the promoter region has inverse results . In addition, PIN1 is likely to be an indispensable orchestrator in the process of oncogene‐driven carcinogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Up-regulation of Pin1 has been observed in many types of cancers including lung, breast, esophageal squamous cell carcinoma (ESCC) and prostate cancers, and is generally regarded as a biomarker for poor prognosis. 6,7 Several studies have reported possible mechanisms of Pin1 up-regulation. For example, increased Pin1 level was found to be increased through the oncogenic Neu/Ras pathway via E2F to promote tumorigenesity in mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%